Diagnostic values of dual focus narrow band imaging and probe-based confocal laser endomicroscopy in FAP-related duodenal adenoma - Pittayanon, Rapat; Rerknimitr, Rungsun; Imraporn, Boonlert; Wisedopas, Naruemon; Kullavanijaya, Pinit (Endoscopy International Open, 2015)
Background and study aims: Familial adenomatous polyposis (FAP) is associated with an increased risk of development of periampullary and nonampullary adenoma. Either routine biopsy or endoscopic removal of the lesion is generally required to identify the presence of adenoma. Because the risk of tissue sampling from the ampulla is high and nonampullary polyps are sometimes numerous, resection of all the lesions is time-consuming. This study aimed to evaluate the diagnostic values of duodenal adenoma by dual focus NBI (dNBI) and probe-based confocal endomicroscopy (pCLE) in FAP patients.Patients and methods: The authors conducted a diagnostic study in a single tertiary-care referral center. Surveillance esophagogastroduodenoscopy with dNBI and pCLE was performed on 26 patients with FAP for real-time adenoma diagnosis by two different endoscopists; one used dNBI and the other pCLE. Histology from the matched lesion was used as the gold standard. Results: A total of 55 matched biopsies (25 ampullas, 30 nonampullas) were performed. The sensitivity, specificity, post predictive value (PPV), negative predictive value (NPV), and accuracy of dNBI vs. pCLE from all duodenal lesions were 96.9 % vs. 93.8 %, 78.3 % vs. 81 %, 86.1 % vs. 88.2 %, 94.7 vs. 89.5 %, and 92.4 % vs. 88.6 %, respectively.Conclusions: For surveillance of periampullary and nonampullary adenoma in patients with FAP, the real-time readings provided a high degree of diagnostic value when histology was used as the gold standard. (Clinical trial registration number: NCT02162173).